2003
DOI: 10.1007/bf03179177
|View full text |Cite
|
Sign up to set email alerts
|

Determination of field size limitations in stereotactic and intensity modulated radiotherapy

Abstract: For dose measurement in small photon fields, different detectors are currently in use: TLD, semiconductor, diamond-detector, film, etc. But for absolute dosimetry, ionization chambers show the most advantages. To meet the basic dosimetrical requirements for lateral electron equilibrium the field size F must not remain under specified values: i.e. 5.2 x 5.2 cm2 for 15 MeV X-bremsstrahlung. As well as increasing the focus-chamber-distance, changing the physical density of the build-up material in the close vicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, irradiated rats revealed a significant depletion in the salivary PH and salivary IgA, compared to control group. Salivary gland injury accompanied with structural modification and functional constraint is a result of radiotherapy in the head and neck area, leading to complications, including mucositis, xerostomia and hyposalivation, where it is not potential to avoid salivary glands from the treatment field (12,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, irradiated rats revealed a significant depletion in the salivary PH and salivary IgA, compared to control group. Salivary gland injury accompanied with structural modification and functional constraint is a result of radiotherapy in the head and neck area, leading to complications, including mucositis, xerostomia and hyposalivation, where it is not potential to avoid salivary glands from the treatment field (12,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Just how small these beams can be with adequate beam coverage and accuracy is an important aspect to investigate. This was the subject of a 2003 report by an overseas contributor, Jenson et al 65 . The authors concluded that the beam size needed to be at least 1 x 1 cm 2 to guarantee sufficient accuracy in the dose calculation.…”
Section: Imrt Set-up Errors and Organ Motionmentioning
confidence: 99%
“…The scatter material made from water-equivalent materials has the disadvantage of being bulky, causing problems with patient comfort and with maintaining contact with the patient's skin (Jornet et al 2004). The volume of the scatter material required can be reduced by increasing the density of the scatter material surrounding the detector by using thin metal caps (Haryanto et al 2002, Jensen et al 2003. Dosimeters with metal caps perform well for medium to large fields; however, the inclusion of these caps results in the overestimation of dose in small fields due to the increased probability of interaction in the cap compared to a water-equivalent material, increasing the amount of scatter reaching the active volume.…”
Section: Introductionmentioning
confidence: 99%